Pilot data findings from the Gothenburg treatment for gaming disorder: a cognitive behavioral treatment manual - Hofstedt, Annika; Mide, Mikael; Arvidson, Elin; Ljung, Sofia; Mattiasson, Jessica; Lindskog, Amanda; Söderpalm-Gordh, Anna (Frontiers in Psychiatry, 2023)
Background: Gaming disorder (GD) is a new diagnosis included in the latest edition of the International Classification of Disease -11. Recently conducted international studies suggest a prevalence rate close to 2% for GD, highlighting the need for effective treatments for this patient population. Internationally there are few studies investigating effective treatments specifically designed for this condition. In this pilot study, we wanted to test a newly developed method, the Gothenburg Treatment for Gaming Disorder (GOT-TO-GO) manual; a 15-week cognitive behavioral therapy treatment for GD. Method: This study utilized a single group design with pretest, post-test and a three- and six-month follow-up, with measures of severity of GD and mood. The participants (n=28) were treatment-seeking adults with GD, aged 17 to 49 years. Results: The results show a statistically significant decrease in symptoms of GD after treatment. Hours of gaming per week also decreased concomitantly with a 100 % increase in non-gaming leisure hours. The decrease in symptoms of GD was maintained at the 3-months follow-up after treatment. Correspondingly we saw a decrease in both depression and anxiety that also was upheld three months after treatment. Conclusion: As GD is a new diagnostic concept more research is needed, also taking psychiatric comorbidity into consideration, to arrive at evidence-based conclusions regarding effective treatments. Considering the promising results in this small pilot study with large behavioral changes and reduced symptoms of GD, upheld at least three months after treatment, a larger randomized controlled study is warranted.